Effects of Petroleum Development on Terrain Preferences of Calving Caribou - Nellemann, Christian; Cameron, Raymond D. (ARCTIC, 1996)
We investigated terrain preferences of caribou (Rangifer tarandus granti) in an oilfield region near Prudhoe Bay, Alaska. Under disturbance-free conditions, the distribution of calving caribou determined by aerial transect surveys was correlated with indices of terrain ruggedness based on map contours. Caribou preferred quadrats dominated by fine-textured rugged terrain, particularly when present in large clusters, and avoided quadrats with flatter terrain. Displacement of maternal females from a zone within 4 km of roads and production-related facilities reduced use of rugged terrain types in that zone by 52%; the remaining preferred terrain was scattered and less accessible. This reduction was accompanied by a 43% increase in caribou use of rugged terrain 4-10 km from surface development. Given that terrain ruggedness is positively correlated with forage quality and biomass availability, combined underuse and overuse of these important habitats may compromise summer nutrition of lactating female caribou, thereby depressing body condition and, hence, subsequent reproductive success. On a étudié les préférences de terrain du caribou (Rangifer tarandus granti) dans une région pétrolifère près de Prudhoe Bay en Alaska. En l'absence de perturbations, la distribution du caribou gravide déterminée par des relevés aériens de transects était corrélée avec les indices d'inégalité du terrain établi d'après des courbes de niveau. Le caribou préférait des quadrats dominés par un terrain légèrement accidenté, surtout lorsque les quadrats formaient de grands groupes, et il évitait ceux où le terrain était plus plat. Le déplacement des femelles gravides hors de la zone située à moins de 4 km de routes et d'installations reliées à la production du pétrole a réduit de 52 p. cent l'utilisation de types de terrain accidenté dans cette zone; le reste du terrain privilégié était éparpillé et moins accessible. Cette réduction s'accompagnait d'une augmentation de 43 p. cent de l'utilisation par le caribou de terrain accidenté situé ...